2017
DOI: 10.3390/ijms18112301
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Biosynthetic System Is Inhibited in Human Glioma Due to EXT1/2 and HS6ST1/2 Down-Regulation

Abstract: Heparan sulfate (HS) is an important component of the extracellular matrix and cell surface, which plays a key role in cell–cell and cell–matrix interactions. Functional activity of HS directly depends on its structure, which determined by a complex system of HS biosynthetic enzymes. During malignant transformation, the system can undergo significant changes, but for glioma, HS biosynthesis has not been studied in detail. In this study, we performed a comparative analysis of the HS biosynthetic system in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…In this report we demonstrate a novel role for HS2ST1 in modulating breast cancer cell invasiveness via central signaling pathways including MAPK and Wnt (Figure 6F). Our findings are in line with studies in glioma, indicating a downregulation of HS2ST1 and other HS sulfotransferases 50 . Mechanistically, HSPGs modulate MAPK signaling, promoting proliferation, migration, and invasion 45,51‐53 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this report we demonstrate a novel role for HS2ST1 in modulating breast cancer cell invasiveness via central signaling pathways including MAPK and Wnt (Figure 6F). Our findings are in line with studies in glioma, indicating a downregulation of HS2ST1 and other HS sulfotransferases 50 . Mechanistically, HSPGs modulate MAPK signaling, promoting proliferation, migration, and invasion 45,51‐53 .…”
Section: Discussionsupporting
confidence: 91%
“…EGFR, known to be overexpressed and activated in approximately 20%‐25% of cancers, 55 acts as a central point for the activation and crosstalk with many signaling pathways relevant to tumor migration and invasion 56 . MAPK and other kinases like phosphatidylinositol‐3‐kinase (PI3‐K) act downstream of EGFR activation, promoting tumor cell migration and invasion 50,57‐59 . In addition, decreased activation or inhibition of p38 MAPK decreases breast cancer metastasis 60 …”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HPSE in U87 glioma cells increases their invasion [17], and in U251n also increased cell invasion, proliferation and anchorage-independent colony formation [20]. We have previously shown that HPSE is down-regulated in gliomas Grade II-IV at the mRNA level, and there is a significant decrease of HPSE protein in tumor and paratumorous glioblastoma tissues compared with the normal tissue [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a significant decrease of mRNA levels of HPSE in Grade II-IV gliomas and heterogeneous distribution of HPSE protein in primary glioblastomas were demonstrated [19]. To investigate a hypothesis on a potential negative effect of anti-GBM treatment on HPSE and HS content and distribution in GBM tissues, we collected matched pairs of primary and relapsed GBM tumors from the same patient (n = 8).…”
Section: Chemoradiotherapy Affects Intertumor Heterogeneity Of Hpse Cmentioning
confidence: 99%
See 1 more Smart Citation